Air Pollution Monitoring System Based on IoT with Cloud - Yossy, Emny Harna; Maulana, Arya; Prastyantoro, Ramadhani (LPPM Universitas Islam 45 Bekasi, 2021)
Air pollution kills about seven million people worldwide every year. In Indonesia itself, especially the city of Jakarta, Jakarta's air quality has been ranked as the tenth worst in the world. The purpose of the research is to design an air pollution monitoring system that can help the community to know the level of pollution in their area. The system development method uses a system development life cycle, namely the waterfall. The evaluation method uses blackbox testing for the system and eight golden rules for the user interface. The result achieved is a system that can monitor IoT-based air pollution with the cloud. This system uses several technologies such as Google cloud platform which consists of IoT Core, Pub Sub, Firestore Database, and Google Cloud Function. The MQ 135 temperature sensor and ESP 32 module are also used to be able to read air pollution conditions and send it to the cloud. The conclusion of this study is that the system created can be easily accessed by users to be able to determine IoT-based air quality.